(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the role of Inquiry-Based Learning (IBL) in fostering critical thinking and decision-making skills among high school students. It examines existing literature on IBL, discusses the methodologies for its implementation, and presents results from various studies. The article further analyzes the effectiveness of IBL in enhancing students’ ability to think critically and make informed decisions. Finally, it offers recommendations for educators to integrate IBL into their teaching practices effectively. The study underscores the need for interactive and student-centered approaches to learning, ensuring students are equipped with essential cognitive skills for future academic and professional endeavors.